THE ROLE OF EDUCATIONAL GAMES IN EFL LEARNING - Davlatova Dilfuza Xolmurod qizi; Xolmuradova D. X. (Academia Science Repository, 2023)
The article provides a review of the problems with employing games in the classroom to help EFL (English as a Foreign Language) students perform better. Its major goal is to establish the significance of educational game use as a teaching strategy in EFL sessions. According to the majority of research, playing these games helps EFL students overcome their shyness and motivates them to use the language as a method of contact with people in a variety of settings. Additionally, research demonstrates that employing games in EFL classes is advantageous for teachers since they may transform the teaching process from teacher-centered into learner-centered and assign most of the responsibility to the student.